Back to the future: returning to silver-backed money in Sri Lanka. Issue 1 (7th January 2019) - Sinna Lebbe, Suhail; Mohamad, Azhar; Mohammad Sifat, Imtiaz
Abstract : Purpose: The purpose of this paper is to investigate the drivers of the behaviour intention to use the Silver-Backed Mobile Payment System (SBMPS) among the residents of Kattankudy, Sri Lanka. Design/methodology/approach: Based on technology adoption model theory, a conceptual framework was devised, which was later tested via structural equation modelling (SEM) using valid responses from a survey questionnaire. Findings: The results indicated that perceived usefulness and subjective norms have positive relationships and perceived risk a negative relationship with people's behavioural intention to adopt SBMPS. In addition, the respondents were primarily motivated by faith (Islam) and also by economic advantages to adopt SBMPS. Research limitations/implications: Religion, culture, gender, income level, age and educational level could be used as moderating factors for better understanding of people's behaviour intentions. A Multi-cultural demographic may shed further light. Social implications: This paper not only makes awareness of the importance of real (commodity) money but also provides the understanding of people's willingness and the underlying motivations to practically implement the system without threatening the legal tender. Originality/value: Extant research has mainly focused on the validity and the conceptual ideas to return to gold and silver money. This paper has been an extension to practically implement real money without threatening the legal tender by investigating the determinants of people's willingness to return to silver money and understanding their motivations underlying those decisions